Intersections between Iconographic and Gendered Approaches to Biblical Interpretation - DiPalma, Brian Charles (2017)
This paper explores the intersections between two approaches to biblical interpretation: iconographic and gendered approaches. Focusing on the ways that visual images from the ancient Near East have been incorporated in studying gender in the Hebrew Bible, I identify four intersections. These examples demonstrate that participating in an iconographic turn is an important way that gender studies in the Hebrew Bible can develop. I also seek to show that the interactions can be mutually fruitful. In other words, including gender as an area of inquiry is a way that the iconographic turn itself can develop in biblical studies.
Keywords: Vision; Ikonographie; Hermeneutik; Ancient Near Eastern iconography -- Hebrew Bible -- gender -- feminist criticism -- queer criticism -- masculinity studies